Fabrication of anisotropic wetting surface with asymmetric structures using geometrical similarity and capillary force - Ye-Eun Lee (Micro and Nano Systems Letters, 2019)
Abstract In the present study, we proposed a fabrication process of anisotropic wetting surfaces with asymmetric grooved parallelogram structures employing basic MEMS processes and micro transfer molding process. A Si substrate and a PDMS mold from Si master were easily self-aligned due to geometrical similarity (all Si wafer have same crystal planes) so that parallelogram microchannels could be formed between the Si substrate and PDMS mold. The parallelogram channels were filled with SU-8 via capillary force, and then the SU-8 parallelogram structures were transferred to an adhesive polymer film. Finally, we obtained an anisotropic wetting surface with SU-8 parallelogram structures, which showed the characteristics of anisotropic wetting and asymmetric flow. The liquid droplets could easily wet in the longitudinal direction of the structures, and the asymmetric flow characteristics of the droplets in the direction perpendicular to the longitudinal direction of the structures could be observed.